What does the future hold for a thermophilic and widely introduced gecko, Tarentola mauritanica (Squamata: Phyllodactylidae)? - Catarina Rato; Iolanda Silva-Rocha; Neftalí Sillero (Biological Invasions, 2024)
The continuous growth and movement of the human population is increasing the frequency of translocating species from their native ranges to novel environments. However, biological invasions offer a rare opportunity to investigate how species can colonise and adapt to new conditions. In that sense, Ecological Niche Models (ENMs) can be a powerful tool to predict where invasive species will spread over the next decades, although they depend heavily on climatic niche conservatism between native and exotic ranges. To reduce these uncertainties, ENMs can be refined by accounting for dispersal constraints. The common wall gecko, Tarentola mauritanica is a native and widespread Mediterranean lizard that has been introduced across different tropical and sub-tropical regions. In this study, we aim to predict the potential and future distribution of T. mauritanica geckos using correlative models, its potential colonization regions under a dispersal model, and the niche overlap between native and introduced populations. The correlative models predict that the most suitable geographic areas for this gecko correspond to Mediterranean-type ecosystems, such as California, central Chile, the Cape Region of South Africa, around the Caspian Sea, south-eastern Asia, and south-western and southern Australia. The species distribution models projected to 2061–2080, forecast that the range of T. mauritanica is likely to shift towards northern latitudes but, surprisingly, not to expand. According to the dispersal models, T. mauritanica will be able to colonise a similar geographic range compared to the one obtained with the correlative models for the future. Finally, the niche overlap results demonstrate that T. mauritanica ’s realised niche has not been conserved over space, as the naturalised climatic niche of the introduced populations differs significantly from its native one. The latter results suggest that there has been no climatic niche conservatism during the several introductions of T. mauritanica and that this species seems to be able to cope with novel and more humid environments, typical from the tropics.

Reconstructing the complex colonisation histories of lizards across Mediterranean archipelagos - Stéphanie Sherpa; Daniele Salvi; Iolanda Silva‐Rocha; Thibaut Capblancq; Josephine R. Paris; Miguel Angel Carretero; Gentile Francesco Ficetola (Journal of Biogeography, 2024)
Aim The Mediterranean Basin is a global biodiversity hotspot and has one of the longest histories of human–biota interactions. Islands host a large fraction of Mediterranean diversity and endemism, but the relative importance of natural versus human‐mediated colonisation processes in shaping the distribution and genetic structure of Mediterranean island fauna remains poorly understood. Here, we combine population genomics, demographic models and palaeoshoreline reconstructions to establish the island‐colonisation dynamics of wall lizards in Mediterranean archipelagos. Location Four Mediterranean archipelagos in Italy and Croatia. Taxon The wall lizard Podarcis siculus. Methods We used ddRAD sequencing to genotype 140 lizards from 23 island and mainland populations. Analyses of admixture and site frequency spectra were used to reconstruct population structure, demographic history and variation of gene flow through time. Genomic results were integrated with palaeogeographical reconstructions and were compared to archaeological evidence of human presence on these islands. Results Although many island populations of this species are assumed to be non‐native, we find that many islands were colonised long before any known human settlements (230,000–12,000 years ago). This natural colonisation most likely occurred through land bridges during glacial marine regression or by over‐sea rafting. On the other hand, islands distant from the continent were often colonised recently, and some of the estimated island colonisation times match historical records of human arrival. We also determine that long‐established island populations generally show lower genetic diversity compared to proximate mainland populations, contrary to recently colonised islands that must have experienced higher rates of post‐colonisation gene flow. Main Conclusion Our integrated approach provides us with the power to accurately quantify the origin, timing and mode of island colonisation. This framework helps to clarify the biogeographical and evolutionary history of island populations, with important implications for conservation and management of island biodiversity.

Conditioned medium of mesenchymal stem cells: application in mares with endometrial fibrosis - Fabiano Trevisan da Rocha; Janislene Mach Trentin; Henrique Boll de Araújo Bastos; Rômulo Oliveira Fernandes da Silva; Matheus Souto de Freitas; Rodrigo Costa Mattos; Nélson Alexandre Kreztmann Filho; Mara Iolanda Batistella Rubin (Journal of Equine Veterinary Science, 2023)

Horizon scanning for invasive alien species with the potential to threaten biodiversity and human health on a Mediterranean island - Jodey Peyton; Angeliki F. Martinou; Oliver L. Pescott; Monica Demetriou; Tim Adriaens; Margarita Arianoutsou; Ioannis Bazos; Colin W. Bean; Olaf Booy; Marc Botham; J. Robert Britton; Javier Lobon Cervia; et al. (Biological Invasions, 2019)